Profiles of school readiness skills among low-income preschoolers in the U.S. - Walker, Aimée Kleisner, author; MacPhee, David, advisor; Barrett, Karen Caplovitz, committee member; Henry, Kimberly, committee member; Lunkenheimer, Erika, committee member (Colorado State University. Libraries, 2013)
The current population-based study employs a person-oriented approach to examine patterns of functioning across school readiness domains (pre-academic competence, self-regulatory abilities, and problematic social behaviors) at kindergarten entry within a national sample of low-income children (N = 2,073), utilizing data from the Early Head Start Research and Evaluation Project (EHSREP; 1996-2010). This study is the first to employ factor mixture analyses (FMA), a hybrid of latent transition analysis and factor analysis, to explore at-risk children's school readiness profiles and assess whether these profiles are salient indicators of academic and social functioning in fifth grade. Results from the FMA identified two distinct classes. Specifically, class 1 (poor school readiness profile) exhibited greater weaknesses in their school readiness profiles than class 2 as demonstrated by higher scores on problematic behavioral indicators that thwart early school success, and lower scores on pre-academic competences and regulatory abilities that support early school success. Additionally, class 1 displayed higher within-class correlations among school readiness indicators on each factor than class 2. Evidence for the predictive validity of these classes was found: In fifth grade, class 1 showed significantly lower scores on academic indicators of school success (e.g., reading, math), and significantly higher scores on indicators of maladaptive social functioning. Notably, class 1 demonstrated lower reading scores and higher scores on problematic behaviors (e.g., attention problems, aggressive behavior) than any of the high-risk groups identified in the final report of the EHSREP). These findings support the putative dynamic connections that exist across readiness domains, suggesting that at-risk children's school readiness is not simply an additive model. These findings point to analytic strategies that better illuminate variations in school readiness within high-risk samples, and also suggest that a significant minority of low-income preschoolers need intensive intervention if they are to succeed in school.
Keywords: factor mixture modeling; Early Head Start; school readiness; 5th grade outcomes; at-risk